Case Report: Analysis of Circulating Tumor Cells in a Triple Negative Spindle-Cell Metaplastic Breast Cancer Patient - Rossi, Tania; Palleschi, Michela; Angeli, Davide; Tebaldi, Michela; Martinelli, Giovanni; Vannini, Ivan; Puccetti, Maurizio; Limarzi, Francesco; Maltoni, Roberta; Gallerani, Giulia; Fabbri, Francesco (Frontiers in Medicine, 2021)
Circulating tumor cells (CTCs) are a rare population of cells found in the bloodstream, and represent key players in the metastatic cascade. Their analysis have proved to provide further core information concerning the tumor. Herein, we aim at investigating CTCs isolated from a 32-years-old patient diagnosed with triple negative spindle-shaped metaplastic breast cancer (MpBC), a rare tumor poorly responsive to therapies and with a dismal prognosis. The molecular analysis performed on the primary tumor failed to underline effective actionable targets to address the therapeutic strategy. Besides the presence of round-shaped CTCs, cells with a spindle shape were present as well, and through molecular analysis we confirmed their malignant nature. This aspect was coherent with the primary tumor histology, proving that CTCs are released regardless of their morphology. Copy number aberration (CNA) profiling and variant analysis using next-generation sequencing (NGS) showed that these cells did not harbor the alterations exhibited by the primary tumor (PIK3CA G1049A mutation, MYC copy number gain). However, despite the great heterogeneity observed, the amplification of regions involved in metastasis emerged (8q24.22-8q24.23). Our findings support the investigation of CTCs to identify alterations that could have a role in the metastatic process. To the best of our knowledge, this is the first examination of CTCs in a MpBC patient.